Queered online pandemic relationships mobile expressions of intimacies, care, and emotion work - Labor, Jonalou S. (Plaridel, 2021)
Access online through this link: https://www.plarideljournal.org/article/queered-online-pandemic-relationships-mobile-expressions-of-intimacies-care-and-emotion-work